2021
DOI: 10.2337/dc20-1712
|View full text |Cite
|
Sign up to set email alerts
|

Serum Galectin-3 and Subsequent Risk of Coronary Heart Disease in Subjects With Childhood-Onset Type 1 Diabetes: A Cohort Study

Abstract: OBJECTIVE To study whether serum galectin-3 and other biomarkers of inflammation predict coronary heart disease (CHD) in subjects with long-standing childhood-onset type 1 diabetes. RESEARCH DESIGN AND METHODS A population-based nationwide cohort of 299 subjects with type 1 diabetes diagnosed in Norway at <15 years of age during 1973–1982 was examined in 2002–2003 at a mean age of 33 years (range 21–44), with mean diabetes duration of 24 years (range 19–30). Subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…Hyperglycemia induced inflammation, oxidative stress and hypercoagulability is also discussed, leading to micro- and macrovascular complications [ 41 ]. Our study is observational, but our findings in this study and in a former study may support these hypotheses [ 21 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hyperglycemia induced inflammation, oxidative stress and hypercoagulability is also discussed, leading to micro- and macrovascular complications [ 41 ]. Our study is observational, but our findings in this study and in a former study may support these hypotheses [ 21 ].…”
Section: Discussionsupporting
confidence: 84%
“…The primary outcome was an incident AMI event using the International Classification of Diseases 9th revision (ICD-9) codes 410 or ICD-10 codes I21–I22 [ 21 ]. First hospitalization with a primary or secondary diagnosis of AMI or death with AMI as the underlying cause, whichever occurred first, was defined as the first event of AMI.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, KLF3 knockout mice did not gain weight after feeding on a high-fat diet [24]. KLF3 was also shown to inhibit beiging of white adipose tissue in mice [22] and directly repress galectin-3, a regulator of inflammation in metabolic tissues [39,40], thus protecting pancreatic beta cells against IL-1β cytotoxicity [41].…”
Section: Discussionmentioning
confidence: 99%
“…Ozturk et al performed coronary CT scans on 158 patients with T2D and reported that Galectin-3 was positively correlated with the number of coronary arteries with atherosclerosis [ 63 ]. Saeed et al followed up a population-based nationwide cohort in Norway, and found that after the adjustment of conventional risk factors, Galectin 3 was significantly associated with the risk of future coronary heart disease (CHD) and may help to predict the occurrence of CHD in patients with T1D [ 64 ]. These findings suggest that Galectin-3 could be a predictor for coronary atherosclerosis in patients with T1D or T2D.…”
Section: Galectin-3 In Diabetes Complicationsmentioning
confidence: 99%